Upaya Pemerintah Desa Patemon dalam Pemberantasan Minuman Keras Berdasarkan Peraturan Daerah Kabupaten Probolinggo Nomor 4 Tahun 2019 tentang Pengendalian dan Pengawasan Minuman Beralkohol - M. Rohim (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
This study aims to analyze the efforts of the Patemon Village Government in eradicating alcoholic beverages based on Probolinggo Regency Regional Regulation Number 4 of 2019 concerning the Control and Supervision of Alcoholic Beverages and to identify obstacles faced in its implementation. The research applies an empirical juridical method with a qualitative approach using interviews, observations, and documentation techniques. The results indicate that the village government’s efforts are carried out through preventive, persuasive, and coordinative measures. Preventive actions include regulation, socialization, community guidance, and involvement of religious and community leaders. Persuasive efforts are conducted through familial and religious approaches toward offenders and residents. Coordinative measures are implemented in collaboration with security officers such as Linmas, Bhabinkamtibmas, and Satpol PP. However, policy implementation still faces several obstacles, including limited village authority in law enforcement, low public legal awareness, economic factors, limited administrative resources, and clandestine distribution of alcoholic beverages from outside the village. Therefore, strengthening villagelevel regulations, enhancing inter-institutional coordination, and increasing community participation are necessary to ensure more effective alcohol control.